2019
DOI: 10.1038/s41598-019-51749-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and evolution of glucosinolate sulfatases in a specialist flea beetle

Abstract: Glucosinolates, a characteristic group of specialized metabolites found in Brassicales plants, are converted to toxic isothiocyanates upon herbivory. Several insect herbivores, including the cabbage stem flea beetle (Psylliodes chrysocephala), prevent glucosinolate activation by forming desulfo-glucosinolates. Here we investigated the molecular basis of glucosinolate desulfation in P. chrysocephala, an important pest of oilseed rape. Enzyme activity assays with crude beetle protein extracts revealed that gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 50 publications
1
19
2
Order By: Relevance
“…Compared to previous studies with P. chrysocephala adults (Beran et al, 2018; Ahn et al, 2019), plant myrosinase activity had less impact on the metabolic fate of ingested glucosinolates in P. armoraciae adults. In quantitative studies, plant myrosinases hydrolyzed approximately 75% of the total ingested glucosinolates in P. chrysocephala , whereas only about 10% of ingested allyl glucosinolate were hydrolyzed in P. armoraciae .…”
Section: Discussioncontrasting
confidence: 86%
“…Compared to previous studies with P. chrysocephala adults (Beran et al, 2018; Ahn et al, 2019), plant myrosinase activity had less impact on the metabolic fate of ingested glucosinolates in P. armoraciae adults. In quantitative studies, plant myrosinases hydrolyzed approximately 75% of the total ingested glucosinolates in P. chrysocephala , whereas only about 10% of ingested allyl glucosinolate were hydrolyzed in P. armoraciae .…”
Section: Discussioncontrasting
confidence: 86%
“…In previous quantitative feeding studies with P. chrysocephala, plant myrosinases hydrolyzed approximately 75% of the total ingested glucosinolates (Beran et al, 2018;Ahn et al, 2019), whereas only about 10% of ingested allyl glucosinolate were hydrolyzed in our quantitative study with P. armoraciae. (A) Beetles were allowed to feed for 1 min on Arabidopsis leaves with (wild type) or without (tgg) myrosinase activity and were dissected into gut and rest of body 5 min later (n = 3 per plant genotype).…”
Section: Discussionmentioning
confidence: 43%
“…Both adults and larvae of P. chrysocephala cause crop damage; adult beetles feed on leaves, whereas the larvae mine within the stems and petioles (Vig, 2003; Williams, 2010). Previous research demonstrated that P. chrysocephala uses at least three different strategies to overcome the GLS‐myrosinase defense of their host plants (Ahn et al., 2019; Beran et al., 2018) (Figure 1a). Two distinct mechanisms prevent the hydrolysis of GLS, i.e .…”
Section: Introductionmentioning
confidence: 99%
“…Herbivorous insects have evolved diverse strategies to minimize their exposure to toxic ITCs (Jeschke et al., 2016a; Winde & Wittstock, 2011). For example, diamondback moth larvae, desert locusts, and cabbage stem flea beetles prevent the hydrolysis of ingested GLS by plant myrosinases through conversion to desulfo‐GLS (Ahn et al., 2019; Falk & Gershenzon, 2007; Heidel‐Fischer et al., 2019; Ratzka et al., 2002), and butterflies in the subfamily Pierinae evolved a biochemical mechanism that promotes the formation of less toxic nitriles instead of ITCs upon GLS hydrolysis (Edger et al., 2015; Wittstock et al., 2004). Other herbivores tolerate ITCs or evolved efficient glutathione‐S‐transferases, which reduce the amounts of free ITCs by conjugating them to glutathione (Gloss et al., 2014; Jeschke et al., 2017).…”
Section: Introductionmentioning
confidence: 99%